Determining The Existence Of Knowledge Management Processes Among Academicians - Nawi, Haslinda Sutan Ahmad; Shukor, Nur Syufiza Ahmad; Basaruddin, Suzana; Rahim, Nasrudin Md; Hassan, Rohaya Abu; Jusoff, Kamaruzaman (Journal of Knowledge Management Practice, 2012)
The purpose of this paper is to determine the existence of the Knowledge Management (KM) processes among academicians. The processes of KM studied here are knowledge capturing, organizing, refining and transferring. A questionnaires survey method was adopted ‘and conducted at the Faculty of Industrial Information Technology (FIIT), Universiti Industri Selangor (UNISEL) where academicians at FIIT were selected as samples. There were two groups of academicians responded to the questionnaires: academicians who served in the year 2006; and academicians who served in 2008. Statistical analysis was conducted to the data collected from the questionnaires. The analysis concludes that all the four KM processes exist and being practiced by the academic staff at FIIT at significance level of 0.05. This paper raises awareness on the importance of the KM processes and as knowledge-intensive organization, this helps to provide initial guidelines to the management in order to cultivate the knowledge sharing society among the academicians. This paper is one of the earliest efforts to determine the existence of KM processes at one of the IHL in Malaysia, a subtle KM activities that receives little attention from the academicians.